OC-001 Anti-tnf Withdrawal In Ibd: Initial Results From A Pan-uk Study. (9th June 2014) - Kennedy, NA; Warner, B; Johnston, E; Basquill, C; Harris, R; Lamb, CA; Singh, A; Fadra, AS; Cameron, F; Basavaraju, U; Mason, J; Lithgo, K; et al.
Abstract : Introduction: Infliximab and adalimumab have established roles in IBD therapy. NICE and SMC guidelines mandate reassessment of disease activity after 12 months. Therapy should ordinarily be discontinued where clinical remission and mucosal healing has been achieved. However, there are presently few data about outcomes of anti-TNF withdrawal. Methods: We conducted a retrospective clinical audit of outcomes following withdrawal of anti-TNF therapy. Inclusion criteria were confirmed diagnosis of IBD; ≥12 m continuous anti-TNF therapy; primary withdrawal reason sustained clinical remission (no corticosteroids for 6 m); ≥12 m follow-up post-withdrawal. Relapse was defined as moderate (oral steroids, immunomodulators, recommencement of anti-TNF agent) or severe (hospitalisation, iv steroids, surgical resection). All UK centres were invited to participate. Demographic and phenotypic data plus clinical, laboratory and endoscopic parameters were recorded. Results: 80 cases (62 infliximab; 18 adalimumab) with a median follow-up time of 26 m post drug withdrawal were included in this analysis (59% female; median age at drug withdrawal 32y). All were in clinical remission at withdrawal; 47/80 had normal laboratory parameters (Hb, WCC, plts, Albumin, CRP, FC) prior to withdrawal. 49/80 had endoscopic re-evaluation with mild disease noted on 9/50 and moderate on 1. 23/70 (33%; 2/23 severe) of patients with Crohn's disease relapsed by 12 months and 49% relapse (3/35 severe) by 24 months (Fig 1, median time to relapse 10.4 m). Younger age at diagnosis (p = 0.017) and elevated WCC (p = 0.025), but not CRP or faecal calprotectin, were predictive of relapse. 4/10 (none severe) with UC/IBDU had relapsed by 12 and 24 months. Anti-TNF therapy was re-introduced in 30 patients following relapse and was successful in 93%. Conclusion: Planned withdrawal of anti-TNF therapy for sustained clinical remission is associated with a moderate relapse of Crohn's disease in up to half of patients by 2 years. Data collection of an expanded cohort is ongoing around the UK to improve power to dissect predictive factors at time of drug withdrawal. Disclosure of Interest: None Declared.